Exposure assessment of nitrate and phenol derivatives in Tehran's water distribution system - Mahdi Hadi; Parnia Bashardoust; Mehri Solaimany Aminabad; Shahrokh Nazmara; Mohammad Rezvani Ghalhari; Alireza Mesdaghinia; Saeedeh Hemmati Borji (IWA Publishing, 2024)
The presence of organic and inorganic contaminants in drinking water is a global concern. Nitrate and phenol derivatives are examples of pollutants that could be of anthropogenic origin. They are associated with numerous health risks, underscoring the importance of monitoring their presence in drinking water. This study aimed to measure nitrate and phenol derivatives, including 2,4-Dichlorophenol (2,4-DCP), Pentachlorophenol (PCP), 2,4,5-Trichlorophenol (2,4,5-TCP), 2-Chlorophenol (2-CP), 4-Chlorophenol (4-CP), and phenol, in Tehran's water distribution system (WDS). The pollutants in Tehran's WDS were significantly and positively correlated with precipitation. The Hazard Quotient (HQ) and the Excess Lifetime Cancer Risk (ELCR) of the detected pollutants were estimated. The results showed that the regional mean of nitrate and PCP in Tehran's WDS were 35.58±8.71mg L−1 and 76.14±16.93 ng L−1 lower than the guideline values of 50 mg L−1 and 1000 ng L−1, respectively. Some districts exhibited nitrate concentration exceeding the allowable limit by a factor of 1.2 to 2.3. Consequently, the nitrate intake in some districts constituted approximately 50% of the reference dose. While PCP as a phenol derivative with more health concerns was identified in Tehran's WDS, the likelihood of its health effects was determined to be negligible. HIGHLIGHTS Regional disparities were evident for nitrate and phenol derivatives.; Nitrate concentration exceeded 50 mg L−1 in some regions of Tehran.; Nitrate intake in some regions accounted for about 50% of the reference dose.; PCP concentration remained below 1,000 ng L−1 across all regions.; ELCR for PCP was significantly lower than the threshold of 10−6.;